Integration of Electricity Generation from RES Supported by Feed in Tariff in an Organized Electricity Market - Mateska, A.K.; Krstevski, P.; Borozan, V.; Taleski, R. (Institution of Engineering and Technology, 2018)
This paper presents results from a study for integration of electricity from renewable energy sources (RES) supported by Feed in Tariffs (FIT) scheme into the electricity market assuming the existence of an organized electricity market. It also covers identification of the impact of RES to the electricity prices on the day-ahead spot market (DAM). Multiple scenarios with different amount of electricity traded on the DAM and generation from RES are considered in the investigation.
Keywords: Day-ahead market, Electricity markets, Renewable energy sources